Seroprevalence of antibodies against smooth strains of Brucella in Junín sheep from SAIS Túpac Amaru, Peru - Campos L, Daniel (2020)
The aim of this study was to determine the seroprevalence of antibodies against smooth strains of Brucella (B. abortus, B. mellitensis and B. suis) in Junín breed sheep of SAIS Tupac Amaru, Peru. Serum samples (n=926) were analysed with a commercial indirect ELISA kit (IDEXX Brucellosis Serum). Only one sample was positive. The beta-pert stochastic simulation program (@Risk) determined a minimum prevalence of 0.10037% and a maximum of 0.11563%.